The Effect of Green Trust, Brand Image and Product Knowledge on Purchase Decision with Green Price as Moderating Variable (Study of The Body Shop consumers in Indonesia) - Meliyana Rizki Prabaningrum; Pramono Hari Adi; Weni Novandari; Monica Rosiana (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This research is a type of quantitative research on The Body Shop. This study takes the title "The Influence of Green Trust, Brand Image and Product Knowledge on Purchasing Decisions with Green Price as a Moderating Variable" (Case study of The Body Shop consumers) The purpose of this study is to analyze the influence of green trust variables, brand image and product knowledge on purchasing decisions with green price as a moderating variable. The population used in this study were all consumers of The Body Shop products. For data analysis using validity and reliability tests, descriptive tests, classical assumption tests, hypothesis tests. Determination of the sample used purposive sampling. The sample in this study was 120 respondents. The results of the study show that the variables of green trust, brand image and product knowledge have a positive effect on purchasing decisions, while the green price variable moderates brand image and product knowledge on purchasing decisions. The implication of this study is that The Body Shop managers continue to increase green trust in their products through campaigns, empty bottle recycling programs, the use of paper bags. Managers can increase green trust in the minds of consumers by always providing good quality, having stable management and displaying positive and environmentally friendly campaigns so that The Body brand image is always good in the eyes of consumers. In addition, further information about The Body Shop products should be published regularly via the website or advertisements so that more people know about The Body Shop products.